Neuromuscular patterns in chronic ankle instability. Issue 4 (27th March 2011) - Leumann, A; Ebneter, L; Von Tscharner, V; Valderrabano, V
Abstract : Background: Ankle sprains are the most frequent injury in sports. Up to 40% of acute sprains develop chronic ankle instability (CAI). CAI may be seen either as mechanical (ligamentous) instability or functional (neuromuscular) instability. So far, no method is known to objectivate functional instability. Purpose: To measure neuromuscular patterns in patients with mechanical ligamentous CAI. Design: Prospective cohort study. Setting and patients: 15 Patients (age 15–58 years) were included evidencing chronic unilateral mechanical ankle instability undergoing ligament reconstruction. As control, the contralateral healthy ankle and 15 sex- and age-matched participants were used. Interventions: Superficial Electromyography (EMG) analysis of four muscles were recorded: gastrocnemius medialis (GM), tibialis anterior (TA), peroneus longus (PL) and soleus (SO) while the patient performed single stance tests on a Biodex Balance System (BBS). Main outcome measurements: EMG was analyzed by intensity and frequency using Wavelet Transformation. Neuromuscular controal was analyzed by the results of the BBS. Results: CAI patients showed significantly decreased results in neuromuscular ankle joint control correlating to increased ankle pain. EMG analyses showed a significant decrease in frequency recruitment for the PL (average frequency, 138.3 Hz for the unstable ankle versus 158.3 Hz for the contralateral healthy side, p<0.001). Instead, no change in intensity was found for the PL. For the GM, TA, and SO, changes neither for intensity, nor frequency were found. Conclusion: This shift of frequency in the PL muscle due to chronic ligamentous ankle instability is the sign of lower muscle activation coming along with type II muscle atrophy. This is the first study to report on the fact that functional ankle instability may be measured as muscle damage seen by a shift in EMG frequency. Therefore, prevention and rehabilitation of chronic ligamentous instability has to address also a functional chronic muscle damage.